Making sense of the Bible [compact disc, unabridged] : rediscovering the power of scripture today - Hamilton, Adam, 1964- (Harper Audio, 2014)
One of the country's leading pastors and Christian authors, addresses the hot-button issues that plague the church and cultural debate, and answers many of the questions frequently asked by Christians and non-Christians alike. Did God really command Moses to put gay people to death? Did Jesus really teach that everyone who is not a Christian will be assigned to hell? Why would Paul command women to "keep silent in the church?" Who decided which books made it into the scriptures and why?